1993
DOI: 10.1038/bjc.1993.344
|View full text |Cite
|
Sign up to set email alerts
|

Hormone resistant prostatic adenocarcinoma. An evaluation of prognostic factors in pre- and post-treatment specimens

Abstract: Pre- and post-treatment specimens from 47 patients with hormone resistant prostatic carcinoma were compared with each other regarding histological grade and immunoreactivity for p53 protein, neuron specific enolase and c-erbB-2 protein. Significantly more specimens expressed a high malignancy grade when the tumour had become hormone resistant than at the time of initial diagnosis (Gleason P: < 0.0001, WHO P:0.0003). p53 protein immunoreactivity increased significantly with disease progression (P:0.006), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 39 publications
5
24
1
Order By: Relevance
“…Like PAP and PSA, cytokeratins are markers for cell maturity. Like others (Feiner & Gonzales, 1986;Berner et al, 1993) we found reduced or absent expression of AE1/AE3 in poorly differentiated tumours.…”
Section: Statisticssupporting
confidence: 53%
See 2 more Smart Citations
“…Like PAP and PSA, cytokeratins are markers for cell maturity. Like others (Feiner & Gonzales, 1986;Berner et al, 1993) we found reduced or absent expression of AE1/AE3 in poorly differentiated tumours.…”
Section: Statisticssupporting
confidence: 53%
“…However, whereas most recent reports presenting good prognostication using the Gleason system have been performed on prostatectomy specimens, our series is based on pretreatment biopsies characterised by cauterisation artefacts (TUR-P specimens) and scanty material (core biopsies). As in our recent study of hormone-resistant prostatic carcinomas (Berner et al, 1993), we noticed some undergrading by the Gleason system in core biopsies.…”
Section: Statisticsmentioning
confidence: 66%
See 1 more Smart Citation
“…Formalin fixed prehormone treatment and posthormone treatment specimens from 47 patients were negative for HER-2/neu overexpression when they were evaluated by immunohistochemistry. 25 Visakorpi et al found that 0 of 147 prostatic carcinoma specimens exhibited HER-2/neu staining by immunohistochemistry. 34 It is unlikely that a water bath method of antigen retrieval alone contributed to the increased HER-2/neu expression in our study, because microwave 13 and vegetable-steamer techniques also yielded results similar to the results achieved with the water bath method.…”
Section: Discussionmentioning
confidence: 99%
“…15,42 Its prognostic significance in cancer of urinary bladder carcinoma and prostate is still controversial. [43][44][45][46] In the current study, c-erb B-2 has no prognostic impact on the clinical outcome of patients. Therefore, the expression of c-erb B-2 may not play an important role in the aggressive behavior of Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%